Preparation method and application of mineralized rigid hydrogel
By preparing CaSO4@PLLA nanofiber membranes through electrospinning and cross-linking them in a specific solution to form a high-rigidity mineralized hydrogel, the problems of low mineralization efficiency and limited stiffness improvement were solved, and effective repair of osteoporotic bone defects was achieved.
Patent Information
- Application Number
- CN202511150214.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-18
- Publication Date
- 2025-12-02
AI Technical Summary
Existing mineralization-enhanced hydrogels have low mineralization efficiency, are prone to swelling when immersed in low-concentration simulated body fluids for extended periods, and have limited stiffness improvement, thus failing to effectively promote the regeneration and repair of osteoporotic bone defects.
CaSO4@PLLA nanofiber membranes were prepared by electrospinning, and after being cut into short fibers, they were crosslinked in a hydrogel precursor solution containing CS, β-GP and SA. Subsequently, they were soaked in a solution of calcium chloride and disodium hydrogen phosphate to form a high-rigidity mineralized hydrogel, which promoted osteogenic differentiation and inhibited osteoclast formation.
It significantly improves the stiffness of hydrogels, promotes osteogenic differentiation of stem cells and inhibits osteoclast formation, providing an effective scaffold for repairing osteoporotic bone defects.
Smart Images

Figure CN121041504A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedicine, and in particular to a method for preparing and applying a mineralized rigid hydrogel. Background Technology
[0002] Bone tissue engineering technology integrates seed cells, bioactive factors, and biomimetic scaffold materials in three dimensions to construct bioactive bone substitutes in vitro, providing an innovative solution for the repair of osteoporotic bone defects. Of particular note is the significant mechanical response characteristics of bone tissue; its cell populations can precisely sense the physical properties of the scaffold material (including stiffness and surface topology) through specific mechanoreceptors, thereby activating downstream osteogenic differentiation signaling pathways.
[0003] Hydrogel materials are considered ideal scaffold candidates due to their structural similarity to the natural extracellular matrix and their tunable mechanical properties. However, generally, enhancing the stiffness of hydrogels mainly relies on increasing crosslinking density and adding inorganic fillers (including direct doping and biomineralization). This approach may not only compromise the biocompatibility of the material, but also has significant limitations in improving its mechanical properties. Among these methods, mineralization, as one of the most powerful ways to enhance stiffness, improves the stiffness of hydrogels by mineralizing them in simulated body fluids or in solutions containing other mineralizing elements (calcium salts, phosphates, enzymes that catalyze mineralization, or other small molecules). However, existing mineralization-enhanced hydrogels suffer from problems such as low mineralization efficiency, limited stiffness improvement, and swelling and structural damage caused by prolonged immersion in low-concentration simulated body fluids.
[0004] Furthermore, the maintenance of skeletal homeostasis depends on the precise regulation of the osteoblast-osteoclast network, a complex cellular communication system dynamically regulated through multi-level molecular signaling. Osteoblast lines secrete a complete spectrum of signaling molecules to guide osteoclast activity, including positive regulatory pathways such as the receptor activator of nuclear factor κB ligand (RANKL) / macrophage colony-stimulating factor (M-CSF) differentiation-promoting axis, the chemokine network (chemokine (C-X3-C motif) ligand 1 (CX3CL1) / monocyte chemotactic protein-1 (MCP-1)), and inhibitory regulatory networks such as osteoprotegerin (OPG) / prostaglandin E2 (PGE2) / interleukin-18 (IL-1)8. These molecules not only regulate terminal differentiation of osteoclasts but also finely regulate the homing, survival, and polarization of their precursor cells. Therefore, when using hydrogel materials, it is necessary to consider not only the enhancement of osteogenic efficiency but also whether this osteogenic differentiation can positively regulate bone regeneration around bone defects. Summary of the Invention
[0005] In view of the aforementioned shortcomings of the prior art, the technical problem to be solved by the present invention is that existing mineralized enhanced hydrogels suffer from low mineralization efficiency, swelling and eventual structural damage when immersed in low-concentration simulated body fluids for extended periods, and limited stiffness enhancement. Therefore, the present invention provides a method for preparing and applying a mineralized stiffened hydrogel. Its stiffening effect directly regulates osteogenic differentiation of stem cells and indirectly inhibits osteoclast formation, promoting the regeneration and repair of osteoporotic bone defects. This provides a novel approach for preparing bone regeneration scaffolds for osteoporotic bone defect repair.
[0006] To achieve the above objectives, the present invention provides a method for preparing a mineralized rigid hydrogel, comprising the following steps:
[0007] CaSO4@PLLA nanofiber membranes were obtained by electrospinning.
[0008] After being shredded, the fibers are dispersed into CaSO4@PLLA short fibers using a homogenizer;
[0009] CaSO4@PLLA short fibers were added to a hydrogel precursor solution containing 6.48% w / v CS, 20.00% w / v β-GP, and 2.08% w / v SA. After double-network crosslinking and gelation in the hydrogel precursor solution, the CaSO4@PLLA short fibers at 1.00% w / v... 2+ The release of β-GP in the hydrogel forms pre-mineralized particles, i.e., pre-mineralized nucleated hydrogel;
[0010] Subsequently, the high-rigidity mineralized hydrogels were obtained by soaking them in solutions of calcium chloride and disodium hydrogen phosphate for several hours.
[0011] Furthermore, CaSO4@PLLA nanofiber membranes were obtained by electrospinning. Specifically, 0.1 g of CaSO4 was weighed and placed in 5 mL of hexafluoroisopropanol HFIP, ultrasonically dispersed for 30 min, and then 0.6 g of PLLA (Mw: 300 kDa) and 0.025 g of polyethylene oxide (PEO) were weighed and dissolved in the solution, and stirred until homogeneous.
[0012] CaSO4@PLLA nanofiber membranes were prepared under the following conditions: high voltage electric field strength of 6-10kV, flow rate of 0.5mL / h, drum rotation speed of 1000rpm, receiving distance of 25-30cm, humidity of 45-65%, and room temperature.
[0013] Further, after being shredded, the fibers are dispersed into CaSO4@PLLA short fibers using a homogenizer. Specifically, the prepared fiber membrane is cut into fragments and dispersed in CaSO4-saturated deionized water. The dispersion is then carried out using a homogenizer at 21,000 rpm for 20 minutes to obtain CaSO4@PLLA short fibers.
[0014] Furthermore, the dual network comprises a first network and a second network. The first network is a hydrogel network formed by the hydrophilic-hydrophobic interaction between CS and β-GP after temperature elevation; the second network is composed of SA and Ca released from CaSO4@PLLA short fibers. 2+ Ionic cross-linking occurs through the interaction.
[0015] Furthermore, high-rigidity mineralized hydrogels were subsequently obtained by soaking in solutions of calcium chloride and disodium hydrogen phosphate for several hours. Specifically, the pre-mineralized nucleated hydrogels were soaked in mineralization solutions to obtain high-rigidity mineralized hydrogels, including soaking in solutions of calcium chloride and disodium hydrogen phosphate in sequence for 6 hours to obtain further mineralized hydrogels, thereby changing the stiffness of the hydrogels.
[0016] Furthermore, the amount of CaSO4@PLLA short fibers was set to 0.5-2% w / v.
[0017] Furthermore, the concentration of the calcium chloride solution was 7.7 mM, the concentration of the disodium hydrogen phosphate solution was 4.6 mM, and the Ca / P ratio was 1.67.
[0018] Another preferred embodiment of the present invention provides an application of a mineralized rigid hydrogel for osteogenic differentiated stem cells and for inhibiting the generation of osteoclasts.
[0019] Furthermore, osteogenic differentiated stem cells are bone marrow mesenchymal stem cells.
[0020] Furthermore, the cells used to study osteoclast differentiation inhibition were RAW264.7 macrophages.
[0021] In another preferred embodiment of the present invention, a mineralized rigid hydrogel is provided for promoting osteodifferentiation and inhibiting osteoclast formation, wherein the osteogenic differentiation conditioned medium (CM) is a mixture of paracrine factors produced by osteogenic differentiation of bone marrow mesenchymal stem cells and the culture medium.
[0022] Technical effect
[0023] This invention utilizes a cross-linking agent to pre-mineralize the hydrogel, which then efficiently and significantly enhances the hydrogel's stiffness in the subsequent mineralization solution. This high-stiffness hydrogel significantly promotes osteogenic differentiation of stem cells and regulates osteoclast inhibition, representing a novel approach for constructing scaffolds for osteoporotic bone defect repair.
[0024] The following will further explain the concept, specific structure, and technical effects of the present invention in conjunction with the accompanying drawings, so as to fully understand the purpose, features, and effects of the present invention. Attached Figure Description
[0025] Figure 1These are ordinary optical microscope images of the CaSO4@PLLA short fibers prepared in Example 1 of this invention;
[0026] Figure 2 This is a schematic diagram of the stress-strain curve (A) and Young's modulus (B) of the mineralized rigid hydrogel prepared in Example 2 of the present invention;
[0027] Figure 3 This is a schematic diagram of X-ray diffraction (XRD) testing of the mineralized rigid hydrogel prepared in Example 2 of the present invention;
[0028] Figure 4 This is a schematic diagram of the effect of mineralized rigid hydrogel on promoting osteogenic differentiation of bone marrow mesenchymal stem cells in Experiment Example 1 of the present invention: (A and C) Alkaline phosphatase (ALP) staining and quantification; (B and D) Alizarin Red (ARS) staining and quantification;
[0029] Figure 5 This is a schematic diagram of the indirect inhibition of osteoclast formation by mineralized rigid hydrogel in Experiment Example 2 of the present invention: (A) Expression of osteoclast-related genes; (B and C) Staining and quantification of tartrate-resistant acid phosphatase (TRAP);
[0030] Figure 6 This is a schematic diagram of the in vivo bone defect repair of the mineralized rigid hydrogel in Experiment Example 3 of the present invention: Micro-CT image (A) and quantitative results (B). Detailed Implementation
[0031] To make the technical problems to be solved, the technical solutions, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the present invention.
[0032] In the following description, specific details, such as particular internal procedures and techniques, are set forth for illustrative purposes and not for limitation, in order to provide a thorough understanding of the embodiments of the invention. However, those skilled in the art will appreciate that the invention may be practiced in other embodiments without these specific details. In other instances, detailed descriptions of well-known systems, apparatuses, circuits, and methods have been omitted so as not to obscure the description of the invention with unnecessary detail.
[0033] Example 1: Preparation of CaSO4@PLLA short fibers
[0034] Step 1: Preparation of CaSO4@PLLA fiber membrane
[0035] Weigh 0.1 g of CaSO4 and add it to 5 mL of hexafluoroisopropanol (HFIP). After ultrasonic dispersion for 30 min, add 0.6 g of PLLA (Mw: 300 kDa) (purchased from Jinan Daigang Biotechnology Co., Ltd., China) and 0.025 g of polyethylene oxide (PEO) (purchased from Alfa Aesar, UK, Mw≈5,000 kDa) to the solution and stir until homogeneous. Transfer the polymer mixture to a 10 mL syringe for stable jet electrospinning. The spinning conditions are: needle diameter 18 G, high voltage electric field strength 6-10 kV, flow rate 0.5 mL / h, roller speed 1000 rpm, receiving distance 25-30 cm, humidity 45-65%, and room temperature. After spinning, place the fiber membrane in a vacuum drying oven at room temperature for 3 days to allow residual solvent to evaporate.
[0036] Step 2: Preparation of short fibers of CaSO4@PLLA
[0037] The CaSO4@PLLA fiber membrane was shredded using a slicer with a fixed length of 1 mm, repeated three times. The fiber fragments were dispersed in CaSO4-saturated deionized water and homogenized at 21,000 rpm for 20 minutes to obtain CaSO4@PLLA short fibers. Figure 1 As shown, the short fibers are evenly dispersed, and CaSO4 particles are present inside them.
[0038] Example 2: Preparation of mineralized rigid hydrogel
[0039] Step 1: Preparation of the dual-network hydrogel
[0040] Preparation of single-network hydrogel: 3% w / v CS (200 kDa, Maclean) and 4% w / v SA were dissolved in 0.1 M acetic acid solution. A 1 g / mL β-GP aqueous solution was prepared. 1.08 g of CS solution and 0.4 mL of β-GP aqueous solution were weighed and stirred evenly. Then, 0.1 M acetic acid solution was added to bring the total volume to 2.0 g. The mixture was then placed in a 37°C water bath for 5 min to allow CS and β-GP to gel, and named CG.
[0041] Preparation of the dual-network hydrogel: Weigh 1.08 g of CS solution, 0.02 g of CaSO4@PLLA short fibers, and 0.4 mL of β-GP aqueous solution, stir well, then add 0.52 g of SA solution and stir rapidly until homogeneous. Then place in a 37°C water bath for 5 min to allow CS and β-GP to gel, and SA to react with CaSO4@PLLA short fibers slowly released from them. 2+ Cross-linking yields a pre-mineralized hydrogel, named CSP.
[0042] Step 2: Preparation of mineralized rigid hydrogel
[0043] CG and CSP were mineralized in a single process, namely, in 7.7 mM CaCl2 solution and 4.6 mM Na2HPO4 solution (Ca / P ratio of 1.67) for 6 h each, to obtain mineralized CG and CSP hydrogels, which were named CGM and CSPM, respectively.
[0044] The Young's moduli of the hydrogels prepared in this embodiment for CG, CSP, CGM, and CSPM are (CG: 25.73±4.29 kPa, CSP: 59.97±4.28 kPa, CGM: 234.78±25.20 kPa, CSPM: 428.41±45.71 kPa) (e.g. Figure 2 (As shown). The crystallinity of the hydrogel was tested using the XRD method, and the test results are as follows. Figure 3 As shown, the CSPM group exhibited fine spectral peaks similar to those of hydroxyapatite (HAp), particularly a HAp(211) crystal plane peak at 32° (2θ), with a peak height significantly greater than that of the CG, CSP, and CGM groups. Compared to the CG group, although the overall peak shapes of the CSP and CGM groups gradually became clearer, their overall peak shapes were large enveloping peaks due to the presence of a large amount of organic matter.
[0045] Among them, Young's modulus is a direct measure of stiffness. The larger the value, the greater the stiffness, indicating that pre-mineralization and further in vitro mineralization treatment can significantly enhance the mechanical properties of hydrogels.
[0046] Experimental Example 1: The ability of hydrogels with different mineralization levels to promote osteogenic differentiation of bone marrow mesenchymal stem cells in vitro.
[0047] The dry CG, CSP, CGM, and CSPM samples prepared in Example 2 were sterilized under ultraviolet light for 12 hours. Before cell seeding, all hydrogels were pre-incubated with DMEM / F12 mixed medium at 37°C four times (12 hours apart) to remove harmful substances.
[0048] BMSCs were arranged at a ratio of 2 × 10⁻⁶ per well. 4 Cells were seeded at a density of [number] cells per well on 24-well plates containing CG, CSP, CGM, and CSPM hydrogels. After one day of culture, cell spreading ability was observed. After 7 days of differentiation with osteogenic induction medium, the ability to promote osteodifferentiation was assessed using ALP and ARS staining. Results showed (e.g.) Figure 4As shown in the figure, compared with the CG, CSP, and CGM groups, the CSPM group had the highest cumulative expression of ALP-positive (blue-purple) cells. The ALP expression level in the CSP pre-mineralized group was significantly higher than that in the CG group, while the ALP expression level in the CSPM group was further increased compared to the CSP and CGM groups. In the mid-to-late stage (14 days after osteogenic differentiation), ARS staining revealed that calcium deposition capacity was significantly enhanced by the dual-network CSP pre-mineralized hydrogel compared to the single-network CG group. The mineralization deposition in the CGM and CSPM groups was more uniform and darker in color, especially the CSPM group, which showed greater calcium deposition. These results indicate that mineralized hydrogels have a good ability to promote osteogenic differentiation.
[0049] Experimental Example 2: The inhibitory effect of hydrogels with different degrees of mineralization on osteogenic differentiation induction medium for bone marrow mesenchymal stem cells on osteoclasts.
[0050] After collecting osteogenic induced differentiation CMs from Experiment 1, they were added to macrophage culture medium at a ratio of 2:8, along with 100 ng / mL RANKL osteoclast differentiation inducer. Five days after differentiation, the effect on osteoclast differentiation was detected using TRAP and RT-qPCR. The results are as follows: Figure 5 As shown, mineralization-enhanced CSPM hydrogel upregulated osteogenic differentiation paracrine factors and significantly inhibited TRAP expression compared to the other three groups. Furthermore, gene analysis revealed that osteoclast differentiation-related markers cathepsin K (CTSK), non-receptor tyrosine kinase (SRC), and TRAP genes were all downregulated. The gene expression of upstream key factors in osteoclast differentiation, TNF receptor-associated factor 6 (TRAF 6) and osteoclast differentiation transcription factor activating T cell nuclear factor 1 (NFATc 1), was also downregulated, indicating that mineralization has an indirect inhibitory effect on osteoclast differentiation. This also suggests that osteogenic paracrine factors regulate osteogenic / osteoclast balance by inhibiting the RANKL / nuclear factor κB receptor activator (RANK) / OPG signaling pathway.
[0051] Experimental Example 3: Verification of the In Vivo Repair of Osteoporotic Bone Defects by Mineralized Rigid Hydrogels
[0052] Following the sterilization process of the hydrogel described in Example 1, BMSCs were implanted onto the hydrogel surface, and in vivo transplantation was performed one week after osteogenic differentiation. The animal model used was osteoporotic rats induced by ovariectomy (OVX), with a 4 mm diameter defect created in the rat skull. The 4 mm diameter BMSCs-hydrogel construct was implanted into the defect group. Rats were sacrificed at weeks 4 and 8, and samples were harvested and analyzed using Micro-CT scanning and CTVol software to assess new bone formation. The results showed that ( Figure 6A) Compared to the CG, CSP, and CGM groups, the CSPM group had the largest new bone filling area, and a significantly reduced distance between the two ends was observed in the cross-sectional view. After 8 weeks, the new bone tissue in all experimental groups was greater than that observed at 4 weeks, with the CSPM group exhibiting the strongest accelerated regeneration capacity. Quantitative analysis of bone microstructure parameters showed ( Figure 6 B) The bone volume to total tissue volume (BV / TV) ratios in the CSPM group were 20.12% (4W) and 48.90% (8W), while those in the Control, CG, CSP, and CGM groups were only 0.79% (4W) and 1.82% (8W), 4.06% (4W) and 7.84% (8W), 6.44% (4W) and 14.28% (8W), and 8.81% and 18.24%, respectively. Bone surface area (BS), bone surface density (BSD), bone volume (BV), trabecular thickness (Tb.Th), and trabecular number (Tb.N) showed similar trends. For trabecular spacing (Tb.Sp), the quantitative results in the CSPM group were as low as 0.55 mm (4W) and 0.42 mm (8W), showing significant differences compared to the Control, CG, CSP, and CGM groups. These results indicate that the CSPM group significantly enhanced OBD bone regeneration, and the newly formed bone had good bone microstructure and high bone density.
[0053] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.
Claims
1. A method for preparing a mineralized rigid hydrogel, characterized in that, Includes the following steps: CaSO4@PLLA nanofiber membranes were obtained by electrospinning. After being shredded, the fibers are dispersed into CaSO4@PLLA short fibers using a homogenizer. CaSO4@PLLA short fibers were added to a hydrogel precursor solution containing 6.48% w / v CS, 20.00% w / v β-GP, and 2.08% w / v SA. After double-network crosslinking and gelation in the hydrogel precursor solution, the CaSO4@PLLA short fibers at 1.00% w / v... 2+ The release of β-GP in the hydrogel forms pre-mineralized particles, i.e., pre-mineralized nucleated hydrogel; Subsequently, the high-rigidity mineralized hydrogels were obtained by soaking them in solutions of calcium chloride and disodium hydrogen phosphate for several hours.
2. The method for preparing a mineralized rigid hydrogel as described in claim 1, characterized in that, CaSO4@PLLA nanofiber membranes were obtained by electrospinning. Specifically, 0.1 g of CaSO4 was weighed and placed in 5 mL of hexafluoroisopropanol (HFIP), and ultrasonically dispersed for 30 min. Then, 0.6 g of PLLA (Mw: 300 kDa) and 0.025 g of polyethylene oxide (PEO) were weighed and dissolved in the solution. Mix well; CaSO4@PLLA nanofiber membranes were prepared under the following conditions: high voltage electric field strength of 6-10kV, flow rate of 0.5mL / h, drum rotation speed of 1000rpm, receiving distance of 25-30cm, humidity of 45-65%, and room temperature.
3. The method for preparing a mineralized rigid hydrogel as described in claim 1, characterized in that, After being shredded, the fibers were dispersed into CaSO4@PLLA short fibers using a homogenizer. Specifically, the prepared fiber membrane was cut into fragments and dispersed in CaSO4-saturated deionized water. The dispersion was carried out using a homogenizer at 21,000 rpm for 20 minutes to obtain CaSO4@PLLA short fibers.
4. The method for preparing a mineralized rigid hydrogel as described in claim 1, characterized in that, The dual network consists of a first layer and a second layer. The first layer is a hydrogel network formed by the hydrophilic-hydrophobic interaction between CS and β-GP after temperature elevation. The second layer is composed of SA and Ca released from CaSO4@PLLA short fibers. 2+ Ionic cross-linking occurs through the interaction.
5. The method for preparing a mineralized rigid hydrogel as described in claim 1, characterized in that, Subsequently, high-rigidity mineralized hydrogels were obtained by soaking them in solutions of calcium chloride and disodium hydrogen phosphate for several hours. Specifically, the pre-mineralized nucleated hydrogels were soaked in mineralization solutions to obtain high-rigidity mineralized hydrogels, including soaking them in solutions of calcium chloride and disodium hydrogen phosphate in sequence for 6 hours to obtain further mineralized hydrogels, thereby changing the stiffness of the hydrogels.
6. The method for preparing a mineralized rigid hydrogel as described in claim 1, characterized in that, The amount of CaSO4@PLLA short fiber used is set to 0.5-2% w / v.
7. The method for preparing a mineralized rigid hydrogel as described in claim 5, characterized in that, The concentration of the calcium chloride solution is 7.7 mM, the concentration of the disodium hydrogen phosphate solution is 4.6 mM, and the Ca / P ratio is 1.
67.
8. An application of a mineralized rigid hydrogel, characterized in that, Stem cells used for osteogenic differentiation and inhibition of osteoclast formation.
9. The application as described in claim 8, characterized in that, The osteogenic differentiated stem cells are bone marrow mesenchymal stem cells.
10. The application as described in claim 8, characterized in that, The cells used to study osteoclast differentiation inhibition were RAW264.7 macrophages.
11. A mineralized rigid hydrogel for promoting bone differentiation and inhibiting osteoclast formation, characterized in that, Osteogenic differentiation conditioned medium (CM) is a mixture of paracrine factors produced by osteogenic differentiation of bone marrow mesenchymal stem cells and the culture medium.